A PETROPHYSICAL STUDY OF THE TROODOS OPHIOLITE: ROCKS AND THEIR DENSITIES AND ELASTIC PROPERTIES AT HIGH PRESSURES - Luts B.G.; Kireenkova S.M.; Safarov I.B. (My University, 1999)
This experimental investigation of rocks from the Troodos Massif included a detailed geological study of the rocks and their chemical analyses. The physical properties of rocks, density and P and S velocities, were studied at pressures as high as 1.5 GPa. A geological and velocity structure of the massif was derived as a result of the integrated interpretation of the experimental data. A geodynamic model is proposed for the massif based on a density and velocity inversion recorded at high pressures.